A study of the market reaction towards ninth Malaysia plan announcements in Malaysia / Sharifatul Suhaini Mohd Sharif - Mohd Sharif, Sharifatul Suhaini (2007)
This study investigates the market reactions towards the Ninth Malaysia Plan announcement in Malaysia. This study period covers from September 2005 to May 2006.This study use standard methodology to find the stock reaction towards the announcement. From the 70 companies selected, there was no statistically significant before and on announcement date. However, there is statistically significant after the announcement. This was shown the good movement since the stock price is react the announcement. The result shows there is positive abnormal return performance but not statistically significant result on the announcement day. The cumulative abnormal returns on the announcement day show the positive reaction. Therefore, the finding was support the null hypothesis.